Asymmetric Synthesis of Primary and Secondary β‐Fluoro‐arylamines using Reductive Aminases from Fungi. Issue 9 (19th March 2020) - González‐Martínez, Daniel; Cuetos, Aníbal; Sharma, Mahima; García‐Ramos, Marina; Lavandera, Iván; Gotor‐Fernández, Vicente; Grogan, Gideon
Abstract: The synthesis of chiral amines is of central importance to pharmaceutical chemistry, and the inclusion of fluorine atoms in drug molecules can both increase potency and slow metabolism. Optically enriched β‐fluoroamines can be obtained by the kinetic resolution of racemic amines using amine transaminases (ATAs), but yields are limited to 50 %, and also secondary amines are not accessible. In order to overcome these limitations, we have applied NADPH‐dependent reductive aminase enzymes (RedAms) from fungal species to the reductive amination of α‐fluoroacetophenones with ammonia, methylamine and allylamine as donors, to yield β‐fluoro primary or secondary amines with >90 % conversion and between 85 and 99 % ee . In addition, the effect of the progressive introduction of fluorine atoms to the α‐position of the acetophenone substrate reveals the effect of mono‐, di‐ and tri‐fluorination on the proportion of amine and alcohol in product mixtures, shedding light on the promiscuous ability of imine reductase (IRED)‐type dehydrogenases to reduce fluorinated acetophenones to alcohols. Abstract : Reductive Aminases : A series of enantioenriched primary and secondary β‐fluoroamines can be obtained through a stereoselective reductive amination process catalyzed by different reductive aminases with a selection of amine donors.